Comparison of Levels of Heavy Metals in Nasal Concha Tissues in Rural and Urban Regions - Öner, Fatih; Kurt, Nezahat; Üçüncü, Harun (Research Square Platform LLC, 2024)
Abstract Background: Heavy metal exposure has recently become a problem due to the increasing environmental pollution as urbanization expands. Objective: This prospective case control study was conducted to compare levels of heavy metals in the nasal concha of the patients living in urban and rural who underwent partial inferior concha resection. Methods: Sixty-seven patients were divided into two groups: 38 rural patients and 29 urban patients. Lead (Pb), cadmium (Cd), mercury (Hg), copper (Cu), and manganese (Mn) levels were measured in inferior nasal concha by Inductively Coupled Plasma- Optical Emission Spectrometry. Results: Significance was considered at p < 0.05. The levels of Cu (0.24± 0.048 vs. 0.06± 0.019 µg/g) and Zn (3.29± 0.69 vs. 0.44± 0.14µg/g) of the rural patients were significantly higher compared to urban patients (p<0.001). There was no significant difference in the Cd level between groups. Pb (0.024± 0.009 vs. 0.008± 0.0002 µg/g) and Mn (0.273± 0.01 vs. 0.174± 0.05 µg/g) levels of urban patients were significantly higher than rural patients (p<0.001). Conclusions: Heavy metals accumulate in the nasal concha at different rates in rural and urban areas. Indicating the presence of heavy metals in turbinates and measuring their amount may be helpful for diagnostic purposes in diseases whose etiology is attributed to air pollution; however, the pathophysiology still needs to be clarified.
Keywords: 13. Climate action; 11. Sustainability; 3. Good health